A Solution-Focused Brief Therapy (SFBT) intervention model to facilitate hope and subjective well-being among trauma survivors at community clinics in Gauteng : a mixed methods study - Guse, Tharina (University of Pretoria, 2021)
Thesis (PhD)--University of Pretoria, 2020.